Interoception and dissociation in migraine: a case–control study of chronic and episodic subtypes - Akihiro Koreki; Akihiro Koreki; Vilomi Bhatia; Anne-Marie Logan; Usman Khan; Mitsumoto Onaya; Sarah Garfinkel; Hugo Critchley; Mark Edwards; Niranjanan Nirmalananthan; Mahinda Yogarajah; Mahinda Yogarajah (Frontiers in Neurology)
BackgroundMigraine is one of the most common neurological disorders. Despite advances in understanding of episodic migraine, little is understood about the mechanisms underlying the chronification of migraine. Recently, increasing attention has been given to the potential roles of interoceptive abnormalities and dissociation. Therefore, we sought to explore differences in interoception and dissociation in individuals with episodic and chronic migraine versus individuals without migraine.MethodsA total of 49 participants were analysed of which 26 had migraine (15 chronic and 11 episodic) and 23 were control subjects without a headache disorder. Their objective interoceptive accuracy was assessed using the heartbeat tracking and discrimination tasks. Interoceptive sensibility was assessed using the Porges body perception questionnaire. Interoceptive trait prediction error (ITPE) was calculated based on the discrepancy between their task performance and sensibility. Interoceptive state prediction error (ISPE) was calculated based on the trial-by-trial correspondence between task performance and confidence. The level of their dissociation was assessed via self-report questionnaires.ResultsPatients with migraine had lower interoceptive accuracy for the tracking task (median (interquartile range) 0.50 (0.43) in migraine vs. 0.78 (0.26) in control, Mann–Whitney U test, effect size r = 0.35, p = 0.014), higher interoceptive sensibility (110 (52) vs. 39 (14), r = 0.74, p < 0.001), and greater ITPE than controls (for the tracking task: 1.08 (1.78) vs. − 1.16 (0.88), r = 0.72, p < 0.001 / for the discrimination task: 0.87 (1.44) vs. − 0.62 (0.97), r = 0.69, p < 0.001). Greater ISPE was also found in patients with chronic migraine than episodic migraine (2.30 (0.35) in chronic vs. 1.75 (0.19) in episodic, r = 0.39, p = 0.046). A greater level of somatoform dissociation was found in individuals with chronic, compared to episodic, migraine (27 (11) vs. 22 (2), r = 0.43, p = 0.029).ConclusionThis is the first study to demonstrate interoceptive abnormalities in migraine, specifically of greater interoceptive prediction errors. Interoceptive abnormalities may represent a transdiagnostic mechanisms relevant to the chronification of migraine, and to frequent co-morbidities such as dissociation.